2016
DOI: 10.1007/s10826-016-0531-5
|View full text |Cite
|
Sign up to set email alerts
|

Female Adolescents with Eating Disorders, Parental Psychopathological Risk and Family Functioning

Abstract: Epidemiological studies on adolescents with eating disorders demonstrate a high prevalence of disordered eating behaviors, with a higher prevalence of eating disorders among girls. Several studies have recently demonstrated an association between female adolescents' eating disorders, parental psychopathological risk, and an impaired family functioning with poor quality of the relationships among family members. On the basis of these premises, we conducted a cross-sectional study initially recruiting 243 famili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 64 publications
2
36
0
2
Order By: Relevance
“…In addition, Vidović et al60 suggested that families of adolescents with bulimic diagnosis have a significantly more dysfunctional family background compared to patients diagnosed with AN. The families of bulimic adolescents represented their families as less cohesive, poorly coherent, and badly organized and reported the presence of high levels of family conflict and distress 46,61. Finally, families of adolescents diagnosed with BED showed higher scores of cohesion and flexibility, and similar to families with daughters suffering from AN, they described their family as enmeshed and characterized by poor communication.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition, Vidović et al60 suggested that families of adolescents with bulimic diagnosis have a significantly more dysfunctional family background compared to patients diagnosed with AN. The families of bulimic adolescents represented their families as less cohesive, poorly coherent, and badly organized and reported the presence of high levels of family conflict and distress 46,61. Finally, families of adolescents diagnosed with BED showed higher scores of cohesion and flexibility, and similar to families with daughters suffering from AN, they described their family as enmeshed and characterized by poor communication.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, we used the normative scores for the Italian population for both measures. Furthermore, we did not assess parental psychopathological risk, which could give important information on the development of adolescents’ EDs 46,6971. In addition, the homogeneity of the sample, in terms of cultural, geographical, and socioeconomic status, limits replication of the study in other countries or cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that for these adolescents a vicious circle in which affective and cognitive processes maintain a moral and interpersonal disinvestment, exacerbates their problems during the development. [74][75][76] For these reasons, both these constructs can be important targets of intervention, but more effort should be put to understand how they operate together to prevent antisocial careers.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…Furthermore, in line with the previous literature [23,67,68,73], WBT was also associated with depressive symptoms, poorer self-esteem and impaired social functioning. In addition, data demonstrate that greater family dysfunction is linked with exacerbated risk for psychopathology and eating disturbances among youth [74,75]. Specifically, children in families characterized by rigidity, disengagement, and low cohesion may be most susceptible to eating disorders.…”
Section: Discussionmentioning
confidence: 98%